THE IMPACT OF PRICING STRATEGY AND PROMOTIONAL OFFERS ON CUSTOMER SATISFACTION OF EASY COOKIES TUMALUNTUNG - Pangemanan, Yoel; Worang, Frederik; Saerang, Regina (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the impact of pricing strategy and promotional offers on customer satisfaction of Easy Cookies Tumaluntung. The research focuses on understanding how the company’s pricing strategy and promotional activities influence customer satisfaction levels. A quantitative approach was employed, using a structured questionnaire distributed to 100 respondents who have purchased Easy Cookies products in Tumaluntung. The collected data were analyzed using statistical methods to determine the relationship and influence between variables. The findings reveal that both pricing strategy and promotional offers have a positive and significant impact on customer satisfaction. The results indicate that affordable and perceived fair pricing, combined with attractive promotional offers, effectively enhance customer satisfaction and strengthen customer loyalty toward Easy Cookies. This research highlights the importance of implementing consistent and well-planned pricing and promotional strategies to maintain customer satisfaction and support business growth.